Correlation of measured soft X-ray pulses with modeled dynamics of the plasma focus - Lee, S.; Saw, S. H.; Rawat, R. S.; Lee, P.; Talebitaher, A.; Abdou, A. E; Chong, P. L.; Roy, F.; Arwinder, Singh*; Wong, D. (IEEE, 2011)
The 6-phase Lee model code is used to fit the computed current waveform to the measured current waveform of INTI PF (2.2kJ at 12 kV), a T2 plasma focus device, operated as a source of neon SXR with optimum yield around 2 Torr of neon. The characteristic He-like and H-like neon line soft x-ray (SXR) pulse is measured using a pair of SXR detectors with selected filters that by subtraction has a photon energy window of 900 to 1550eV covering the region of the characteristic neon SXR lines. From the analysis of the fitted current and the measured SXR pulses, the characteristic neon SXR pulses are correlated to the pinch dynamics; and the subsequent slightly harder SXR pulses are correlated to the anomalous resistance phase. The characteristic neon SXR yield is measured; the pulse has a duration of 25 ns. The characteristic neon SXR typically starts 10 ns before the pinch phase and continues through the end of the 10 ns pinch phase, tailing into the anomalous resistance phase. Harder SXR pulses, probably Bremsstrahlung are correlated to the anomalous resistance phase, with the main pulse occurring nearly 200 ns after the characteristic neon SXR pulse.